Plate III: Stomach Corroded by a Poisonous Dose of Sulphuric Acid - Hare, H.A. (Hobart Armory) (A text-book of practical therapeutics, with especial reference to the application of remedial measures to disease and their employment upon a rational basis, 1909)
Plate III is a color illustration depicting the effects of a poisonous dose of sulphuric acid upon the stomach.
Keywords: Care of the sick; Therapeutics; Sulfuric acid